Analisis Pembelajaran Penjasorkes Melalui Media Daring Terhadap Hasil Belajar Kognitif Passing Atas Siswa Kelas Xi SMA Negeri 3 Pati - Mila Anggraheni Puspitasari; Tubagus Herlambang; Buyung Kusumawardhana (YLPK Mahardhika, 2021)
The background to the problem in this study was that during the Covid-19 pandemic, teachers had difficulty providing the online learning process. During this online learning the KKM score for physical education and health services becomes 75. Students are required to be able to take a KKM score above the KKM 75 to complete it. 36 students from the class that can be used as samples have difficulty understanding the Cognitive aspects of Passing on Volleyball Class XI IPA 3 SMAN 3 Pati students in physical education learning through online media. Limited time and obstacles on the internet make student learning outcomes not optimal, so there needs to be improvements in online learning at SMAN 3 Pati. The formulation of the problem in this study is the difficulty of students understanding the cognitive aspects of upper-pass learning. The purpose of this study was to determine that online media can improve the cognitive learning outcomes of class XI students of SMAN 3 Pati. The research method used is descriptive quantitative research method with the One-Shot Case Study approach, the sample of this study was the students of class XI IPA 3 SMAN 3 Pati using purposive sampling technique. The data analysis method used paired sample-t-test with a significant level of 5%. The results of the research of 36 students of class XI IPA 3 (Upper Passing) showed that there was an increase in the results of learning over passing through online learning. The increase in the results of learning over passing was 11%. This study also uses a questionnaire to find out what students think about online learning. The conclusion of this research is that the use of online media can help students in learning over passing through online learning at SMAN 3 Pati. Keywords: Online learning, learning outcomes, volleyball Abstrak Latar belakang masalah pada penelitian ini yaitu dimasa pandemi Covid-19 guru kesulitan dalam memberikan proses pembelajaran daring. Selama pembelajaran daring ini nilai KKM penjasorkes menjadi 75. Siswa dituntut untuk bisa menempuh nilai KKM diatas KKM 75 untuk bisa tuntas. 36 siswa dari kelas yang dapat di jadikan sampel mengalami kesulitan dalam memahami aspek Kognitif Passing Atas Bola Voli Siswa Kelas XI IPA 3 SMAN 3 Pati pada pembelajaran penjasorkes melalui media daring. Terbatasnya waktu dan hambatan dijaringan internet membuat hasil belajar siswa tidak maksimal, sehingga perlu adanya perbaikan dalam pembelajaran daring di SMAN 3 Pati. Rumusan masalah pada penelitian ini adalah sulitnya siswa memahami aspek kognitif pada pembelajaran pasing atas. Tujuan penelitian ini untuk mengetahui media daring dapat meningkatkan hasil belajar kognitif siswa kelas XI SMAN 3 Pati. Metode penelitian yang digunakan yaitu metode penelitian deskriptif kuantitatif dengan pendekatan One-Shot Case Study,sampel penelitian ini adalah siswa kelas XI IPA 3 SMAN 3 Pati menggunakan sampel teknik sampling purposive. Metode analisis data menggunakan uji paired sample-t-test dengan taraf signifikan 5%, hasil penelitian dari 36 siswa kelas XI IPA 3 (Passing Atas) diketahui bahwa adanya peningkatan hasil belajar passing atas melalui pembelajaran daring. Kenaikan hasi belajar passing atas sebesar 11%. Penelitian ini juga menggunakan angket untuk mengetahui pendapat siswa mengenai pembelajaran daring. Simpulan penelitian ini adalah penggunaan media daring dapat membantu siswa dalam belajar passing atas melalui pembelajaran daring di SMAN 3 Pati Kata kunci: Pembelajaran daring, hasil belajar, bola voli